(3TQM GdhGajIs - (3GdnqWnHGnWnHGFj GdHQhLQOj, GHf GdeQJVi, HMQ GdYdhe, eMeO egOj Hf eQJVi Hf eMeO, J (B1212 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf (B... (3GddaX Ef GSJYed ajeG hVY dg, LYd GdebSe eWdb GddaX (B... (3ddeaQO hGdeQcH dCf cdG efgeG jfbSe Edi GdMbjbI hGdeLGRs
(3BNQgG (B:s
(3BNQgG(B: (3dcfg NdGa GdJMbjb eeG jOd Ydi aSGOg CeG JYde HGdVQhQI Cf bUO GdbGFd RjOG (B.. (3GOYGA Cf RjO (B... (3CSO eHGdZI aj OYhi GdTLGYI ceG aj bhdg QCjJ CSOGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 113s
(3GdPQjYI, L (B14: 101s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs